Jute stick derived activated carbon electrodes for capacitive desalination and deionization of heavy metals - Md Shamim Alam; Abu Bin Imran; Chanchal Kumar Roy; Md Shafiul Azam; Al-Nakib Chowdhury (Heliyon)
Capacitive deionization (CDI) based on ion electrosorption has evolved as an environmentally friendly and low-energy important method for solving freshwater scarcity, among other water purification technologies. This study attempted water desalination (Na+/Cl−) and deionization of heavy metals (Ni2+/Cl− and Co3+/NO3−) using an activated carbon (AC) electrode-based CDI system. ACs were synthesized in two different methods, physical activation (ACpa) and physico-chemical activation (ACpc), to investigate the effect of different AC morphologies on electrode performance in removing saline ions and heavy metal ions from water by the CDI method. Electrochemical analyses supported the non-faradic reaction behavior for both electrodes. The maximum BET surface area and total pore volume were obtained to be 1177 m2/g and 0.597 cm3/g, respectively, for ACpc and 523 m2/g and 0.271 cm3/g for ACpa, respectively. The specific capacitance of the ACpc electrode was found to be the highest (161 F/g) compared to that of the ACpa (119 F/g) at a current density of 0.5 A/g. The ACpc electrode exhibits the highest electrosorption capacity of 53.5 mg/g during CDI for removing saline ions from a 100 ppm NaCl solution, surpassing the electrosorption capacities of 39 mg/g obtained by the ACpa electrodes, respectively. The ACpc electrode exhibits a similar trend of the highest electrosorption capacity for removing heavy metal ions (Ni2+ and Co3+) from a 100 ppm NiCl2 and Co(NO3)3 solution, respectively. This research provides an efficient and sustainable technique for improving carbon ion adsorption capabilities and permits eco-friendly recycling of biomass waste for environmental remediation purposes.